Doing Emotional Labour in the Fourth Industrial Revolution (4IR): Is Religious Television a Humanised Workplace? - Nur Kareelawati Abd. Karim (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by WOS/SCOPUS